IgE Sensitization to the Nonspecific Lipid-Transfer Protein Ara h 9 and Peanut-Associated Bronchospasm. (12th September 2013) - Arkwright, Peter D.; Summers, Colin W.; Riley, Beverley J.; Alsediq, Najla; Pumphrey, Richard S. H.
Abstract : Allergen component analysis is now available in many laboratories. The aim of this study was to examine the possible association between peanut allergen IgE components and severity of clinical reactions in patients with a history of peanut allergy. Data and sera collected from 192 patients within the Manchester Allergy Research Database and Serum Bank were used in this retrospective study. Sensitization to peanut specific IgE and Ara h 1, 2, 3, and 8 peanut IgE components, as measured by fluoroenzyme immunoassay, was not associated with anaphylaxis. In contrast, sensitization to the lipid-transfer protein Ara h 9 was significantly more prevalent in patients with peanut-associated bronchospasm (26% versus 9% of patients), even after adjusting for potential confounding effects of age, gender, and severity of concomitant chronic atopic diseases. Patients who were sensitized to Ara h 9 were more likely to have ingested rather than just have had skin contact with peanut and have a more rapid onset of symptoms. These results are consistent with observations that sensitization to heat and protease resistant lipid-transfer protein components of hazelnut, grains, and fruit is predictive of anaphylaxis.